2017
DOI: 10.1038/s41598-017-06552-x
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin ameliorated the behavioral deficits induced by chronic stress in rats

Abstract: The present study aimed to investigate the mechanisms underlying the antidepressant-like effects of puerarin via the chronic unpredictable stress (CUS) procedure in rats. Similar to Sertraline (Ser), Chronic treatment of puerarin (60 and 120 mg/kg, i.g) elicited the antidepressant-like effects by reversing the decreased sucrose preference in sucrose preference test (SPT), by blocking the increased latency to feed in novelty-suppressed feeding test (NSFT) and the increased immobility time in forced swimming tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…These results have been associated with the finding that puerarin increased the time spent in the open arms and the percentage of entries into the open arms of EPM, whereas on the VCT test, it produced an increase in the number of shocks received. In both cases, the effect was similar to that of sertraline, which was used as a positive control drug to generate an anxiolytic effect on both tests [50].…”
Section: Flavonoids With Anxiolytic Effectsmentioning
confidence: 65%
“…These results have been associated with the finding that puerarin increased the time spent in the open arms and the percentage of entries into the open arms of EPM, whereas on the VCT test, it produced an increase in the number of shocks received. In both cases, the effect was similar to that of sertraline, which was used as a positive control drug to generate an anxiolytic effect on both tests [50].…”
Section: Flavonoids With Anxiolytic Effectsmentioning
confidence: 65%
“…The effect of puerarin (1), isolated from P. lobata, on angiotensin II-induced aortic aneurysm formation was also investigated [13]. Although puerarin (1) was reported for its antidepressant-like effects in the chronic unpredictable stress-induced rats [14], its effects on depressive-like symptoms and neurogenesis in OVX mice, the animal model for menopause, have never been investigated. Therefore, the present study aimed to investigate the effects of puerarin (1) on depressive-like behavior in OVX mice, as well as to elucidate the underlying mechanisms related to HPA axis function, using 17β-estradiol (2) as a reference hormone.…”
Section: Introductionmentioning
confidence: 99%
“…The model was prepared based on the previous study 24 and shown in Table 1 . Except for controls, the rats were exposed to the administrations randomly and continuously as below: (1) white noise (approx.…”
Section: Methodsmentioning
confidence: 99%
“…The doses of GRg3 (10, 20 and 40 mg/kg i.g) were selected according to its antidepressant-like effects 15 . Sertraline (15 mg/kg i.g) was prepared as a positive control in the behavioral assessments that based on the previous study 24 .…”
Section: Methodsmentioning
confidence: 99%